Queering/Querying Cosmopolitanism: Queer Spaces in Shanghai - Bao, Hongwei (My University, 2011)
This article examines different types of queer spaces in contemporary Shanghai together with the various same-sex subjects that inhabit these spaces. In doing so, it discusses the impact of transnational capitalism, the nation state and local histories on the construction of urban spaces and identities. Combining queer studies and urban ethnography, this article points to the increasing social inequalities hidden behind the notion of urban cosmopolitanism created by the deterritorializing and meanwhile territorializing forces of transnational capital and the state. It also sheds light on how these various identities and spaces are lived and experienced by ordinary people, as well as possible ways of resistance to the dominant narratives.
Keywords: 306 Kultur und Institutionen; cosmopolitanism; Shanghai; queer space; gay; tongzhi